Data logger technologies for manual wheelchairs: A scoping review - Routhier, François (Assist Technol, 2017)
In recent years, studies have increasingly employed data logger technologies to record objective driving and physiological characteristics of manual wheelchair users. However, the technologies used offer significant differences in characteristics such as measured outcomes, ease of use and level of burden. In order to identify and describe the extent of published research activity that relies on data logger technologies for manual wheelchair users, we performed a scoping review of the scientific and grey literature. Five databases were searched: Medline, Compendex, CINAHL, EMBASE and Google Scholar. The 119 retained papers document a wide variety of logging devices and sensing technologies measuring a range of outcomes. The most commonly used technologies were accelerometers installed on the user (18.8%), odometers installed on the wheelchair (12.4%), accelerometers installed on the wheelchair (9.7%) and heart monitors (9.7%). Not surprisingly, the most reported outcomes were distance, mobility events, heart rate, speed/velocity, acceleration and driving time. With decreasing costs and technological improvements, data loggers are likely to have future widespread clinical (and even personal) use. Future research may be needed to assess the usefulness of different outcomes and to develop methods more appropriate to wheelchair users, in order to optimize the practicality of wheelchair data loggers.